Differential efferent projections of the anterior, posteroventral, and posterodorsal subdivisions of the medial amygdala in mice - Pardo-Bellver, Cecília; Cadiz-Moretti, Bernardita; Novejarque, Amparo; Martinez-Garcia, Fernando; Lanuza, Enrique (Frontiers in Neuroanatomy, 2012)
The medial amygdaloid nucleus (Me) is a key structure in the control of sociosexual behavior in mice. It receives direct projections from the main and accessory olfactory bulbs (AOB), as well as an important hormonal input. To better understand its behavioral role, in this work we investigate the structures receiving information from the Me, by analysing the efferent projections from its anterior (MeA), posterodorsal (MePD) and posteroventral (MePV) subdivisions, using anterograde neuronal tracing with biotinylated and tetrametylrhodamine-conjugated dextranamines. The Me is strongly interconnected with the rest of the chemosensory amygdala, but shows only moderate projections to the central nucleus and light projections to the associative nuclei of the basolateral amygdaloid complex. In addition, the MeA originates a strong feedback projection to the deep mitral cell layer of the AOB, whereas the MePV projects to its granule cell layer. The Me (especially the MeA) has also moderate projections to different olfactory structures, including the piriform cortex (Pir). The densest outputs of the Me target the bed nucleus of the stria terminalis (BST) and the hypothalamus. The MeA and MePV project to key structures of the circuit involved in the defensive response against predators (medial posterointermediate BST, anterior hypothalamic area, dorsomedial aspect of the ventromedial hypothalamic nucleus), although less dense projections also innervate reproductive-related nuclei. In contrast, the MePD projects mainly to structures that control reproductive behaviors [medial posteromedial BST, medial preoptic nucleus, and ventrolateral aspect of the ventromedial hypothalamic nucleus], although less dense projections to defensive-related nuclei also exist. These results confirm and extend previous results in other rodents and suggest that the medial amygdala is anatomically and functionally compartmentalized.